10x-3(2x-5)=2(5x+3)-9

Simple and best practice solution for 10x-3(2x-5)=2(5x+3)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-3(2x-5)=2(5x+3)-9 equation:



10x-3(2x-5)=2(5x+3)-9
We move all terms to the left:
10x-3(2x-5)-(2(5x+3)-9)=0
We multiply parentheses
10x-6x-(2(5x+3)-9)+15=0
We calculate terms in parentheses: -(2(5x+3)-9), so:
2(5x+3)-9
We multiply parentheses
10x+6-9
We add all the numbers together, and all the variables
10x-3
Back to the equation:
-(10x-3)
We add all the numbers together, and all the variables
4x-(10x-3)+15=0
We get rid of parentheses
4x-10x+3+15=0
We add all the numbers together, and all the variables
-6x+18=0
We move all terms containing x to the left, all other terms to the right
-6x=-18
x=-18/-6
x=+3

See similar equations:

| -11d+20=1-9d+1 | | 4x+6=7+4x | | (11k-2)^1/3+1=5 | | 3x+9.7=9x | | 4(3x+2)=-76 | | 0.333333(12x-3)=7 | | -8=3(a-5) | | -12x+4x-5-9=8x-13x+15-8 | | -2x-16=-40 | | 2.5x-4=86 | | 2z+9=-5z+9 | | 8x-3=6-8x | | -4x-4=-4x+2 | | 5(6x+8)=400 | | 15-8c=1-8c | | 2y+4=3X+9 | | 3x+22=5x−17 | | 3x-9+2x=17 | | 70−5k=60 | | -8=(a-5) | | h+6^5=2 | | 135=23x+1+45x | | 4x+12+2x-3=5x+1 | | -13.9+11.8y=12.8y | | 6(7+x)=84 | | q–10=25 | | -2=3v-12-5v | | 8x^2+4x-16=-x² | | q+8=-14 | | -13=2y+-1 | | 4(6x+2)=248 | | -35=1+49n |

Equations solver categories